Design of Low Delay Ring Oscillator Using CMOS - Shiyamala, S; Kavitha, T (International Journal of Engineering and Technology, 2018)
In the Era of digital World, low power applications are the needs of the market to save the resources. Delay elements (e.g. digital clock) are essential parts of such digital applications. Ring oscillators have been used because of their ease of implementation, wide tuning ranges, operating at low voltages and existing possibility of complete integration in standard CMOS processes. It desires at identifying the best possible configuration for the hoop oscillators having the least strength intake and precise delay with lesser sensitivity to the variations inside the temperature and deliver voltage for frequencies of few KHz. while N = 7, forÂ  0.18 Âµm generation , put off is 0.07ns simplest. Compare with N = 3, 14.2 % delay time reduced and 12.6 % lower when N= 7 taken into account.Â